American moonshot : John F. Kennedy and the great space race - Brinkley, Douglas (Harper, an imprint of HarperCollinsPublishers, 2019)
On May 25, 1961, JFK made an astonishing announcement: his goal of putting a man on the moon by the end of the decade. In this engrossing, fast-paced epic, Douglas Brinkley returns to the 1960s to recreate one of the most exciting and ambitious achievements in the history of humankind. American Moonshot brings together the extraordinary political, cultural, and scientific factors that fueled the birth and development of NASA and the Mercury, Gemini and Apollo projects, which shot the United States to victory in the space race against the Soviet Union at the height of the Cold War. Drawing on new primary source material and major interviews with many of the surviving figures who were key to America<U+2019>s success, Brinkley brings this fascinating history to life as never before. American Moonshot is a portrait of the brilliant men and women who made this giant leap possible, the technology that enabled us to propel men beyond earth<U+2019>s orbit to the moon and return them safely, and the geopolitical tensions that spurred Kennedy to commit himself fully to this audacious dream. Brinkley<U+2019>s ensemble cast of New Frontier characters include rocketeer Wernher von Braun, astronaut John Glenn and space booster Lyndon Johnson.